Goldenhar Syndrome-A Case Report - Vidya Holla; Raghavendra Kini; Prassana Kumar Rao; Devika Shetty; Kamakshi Jha; Roopashri Kashyap (Cumhuriyet University, 2019)
Goldenhar Syndrome also called as facio-auriculo-vertebral dysplasia, is a rare syndrome developing from first and second pharyngeal arches during Blastogenesis. It was described by Maurice Goldenhar in 1952. It is characterised by presence of epibulbar dermoids, ear malformations, vertebral anomalies, unilateral facial hypoplasia, and sometimes internal systemic complications. As the molecular basis for Goldenhar Syndrome is unclear, early detection and screening for complications would help the patients to have a normal life.